Sudden cardiac arrest and death in United States marathons - Webner, D.; Duprey, K. M.; Drezner, J. A.; Cronholm, P.; Roberts, W. O. (Medicine & Science in Sports & Exercise, 2012)
Abstract PURPOSE: There is no reporting system for marathon-associated sudden cardiac arrest (SCA) or sudden cardiac death in the United States. The purpose of this study was to estimate and characterize the risk of marathon-related SCA to assist with emergency planning. METHODS: A retrospective Web-based survey was sent out to all US marathon medical directors (n = 400) to gather details of SCA including demographics, resuscitation efforts, mortality, and autopsy results, if available. RESULTS: A total of 88 surveys (22%) were returned from marathons run from 1976 to 2009 for a total of 1,710,052 participants. Risks of SCA and sudden cardiac death were 1 in 57,002 and 1 in 171,005, respectively. Men made up the vast majority of SCA victims (93%, mean age = 49.7 yr, range = 19-82 yr). Arrest site distributions were 0-5, 6-14, 15-22, and 23-26.2 miles. CAD was reported as the cause of death at autopsy in 7 of the 10 fatalities. An automated external defibrillator (AED) was used in 20/30 cases and associated with a higher survival (17/20 survivors vs 3/10 deaths, P = 0.0026). CONCLUSIONS: SCA occurs in approximately 1 in 57,000 marathon runners, is more common in older males, and usually occurs in the last 4 miles of the racecourse. Prompt resuscitation including early use of an AED improves survival. Emergency planning to include trained medical staff and sufficient AEDs throughout the racecourse is recommended.